Efficacy and safety of PD-1/PD-L1 inhibitors as first-line treatment for esophageal squamous cell carcinoma: a systematic review and meta-analysis - Ren, Wei; Zhang, Hanyu; Li, Yixin; Sun, Wu; Peng, Hexiang; Guo, Huangda; Hou, Tianjiao; Wang, Mengying; Hu, Zhendong; Wu, Tao; Liu, Baorui (Frontiers in Immunology, 2025)
PurposeThis study aims to investigate the efficacy and safety of PD-1/PD-L1 inhibitors in the first-line treatment of esophageal squamous cell carcinoma (ESCC) and identify factors influencing efficacy through a meta-analysis of multiple phase 3 randomized controlled trials (RCTs).MethodsA systematic literature search was conducted in Cochrane, PubMed, and Embase databases. Two researchers independently extracted trial data, including efficacy-related outcomes such as overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and duration of response (DoR), along with their subgroup data and safety-related indicators. The overall hazard ratio (HR) and 95% confidence interval (CI) were calculated for OS and PFS, while the overall odds ratio (OR) and 95% CI were computed for ORR to compare the classification and predictive abilities of combined positive score (CPS) and tumor proportion score (TPS) for PD-L1 status. Additionally, survival outcomes across different subgroups were evaluated to explore the potential influencing factors for the efficacy of PD-1/PD-L1 inhibitors in ESCC.ResultsThis meta-analysis included eight phase 3 RCTs encompassing 4,479 participants. PD-1/PD-L1 inhibitors combined with chemotherapy significantly improved OS (HR: 0.68, 95% CI: 0.63-0.74) and PFS (HR: 0.62, 95% CI: 0.58-0.67) in ESCC patients compared to non-combination therapy. Patients with higher PD-L1 expression (CPS>1 or TPS>1) demonstrated superior responses to PD-1/PD-L1 inhibitions, with CPS identified as a stronger predictor of therapeutic benefit, particularly at a threshold of CPS =10. Subgroup analysis revealed that male, Asian, smoking, and liver metastasis patients exhibited a greater trend toward improved disease control with PD-1/PD-L1 inhibitors. However, there was no significant difference in treatment efficacy between immune therapy combined with TP (taxol [paclitaxel] + cisplatin) and FP (5-fluorouracil [5-FU] + cisplatin) regimens (POS=0.51, PPFS=0.11). Finally, PD-1/PD-L1 inhibition was associated with a higher incidence of grade ≥3 adverse events compared to chemotherapy alone (HR: 1.21, 95% CI: 1.07-1.37).ConclusionsThis study confirms that the combination of PD-1/PD-L1 inhibitors and chemotherapy provides significant clinical benefits in ESCC. CPS =10 serves as a key threshold for predicting treatment response. There is a trend suggesting that male, Asian, smoking, and liver metastasis patients may experience better survival benefits, while no significant difference was observed between TP- and FP-based regimens.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024536221